Penerapan Asas Kepastian Hukum dalam Peraturan Menteri Pertanian Nomor 01/PERMENTAN/KB/120/1/2018 Tentang Pedoman Penetapan Harga Pembelian Tandan Buah Segar Kelapa Sawit Produksi Pekebun - Sofia Rahamawati (AGRIFITIA : Journal of Agribusiness Plantation, 2022)
Smallholder oil palm plantations have made a major contribution to the development of the national palm oil industry. However, the policy of developing oil palm plantations continues to be unfavorable to smallholder oil palm farmers, with one example being the right of farmers to earn income and profits as an illustration of guarantees for agricultural product marketing. To realize these farmers' rights, the government established Regulation of the Minister of Agriculture Number 01/PERMENTAN/KB.120/1/2018 concerning Guidelines for Setting the Purchase Price of Oil Palm Fresh Fruit Bunches Produced by Farmers in lieu of Minister of Agriculture Regulation Number 14/Permentan/OT.140/2/2013 concerning Guidelines for Determining the Purchase Price of Oil Palm Fresh Fruit Bunches Produced by Planters, which is considered unable to provide legal certainty because the content material is incomplete and has multiple interpretations. The purpose of writing this law is to analyze the application of the principle of legal certainty in the Regulation of the Minister of Agriculture, Number 01/PERMENTAN/KB.120/1/2018, concerning Guidelines for Determining the Purchase Price of Oil Palm Fresh Fruit Bunches Produced by Planters. The writing of this law uses a normative-juridical method, namely, by examining and understanding the positivization of the principle of legal certainty in statutory regulations. The application of the principle of legal certainty in the substance of the Regulation of the Minister of Agriculture Number 01/PERMENTAN/KB.120/1/2018 concerning Guidelines for Determining the Purchase Price of Oil Palm Fresh Fruit Bunches Produced by Planters has fulfilled the principle of legal certainty, namely protection for both smallholders and smallholders with plasma patterns as well as self-help patterns through partnerships with plantation institutions. In the cooperation agreement between the company and the planters, through the planters' institution, the regional government is authorized as a supervisor, and the government has also regulated the minimum elements for the parties in the cooperation agreement. The regulation regarding supervision and sanctions in this regulation has also clearly stipulated time limits for the implementation of obligations, so that it will be easier for the Governor to supervise and provide sanctions in the event of a violation.   Keywords: Legal Certainty, Smallholders, Oil Palm Plantations.